LEADERSHIP MANAGEMENT SKILLS AND COMPETENCIES FOR ACADEMIC LIBRARY LEADERS IN THE DIGITAL ENVIRONMENT - THAMARAISELVI, Dr. G. (IJRDO - Journal of Social Science and Humanities Research, 2018)
Libraries are defined as non-profit service enterprise which has a particular management process, just like for profit. In this Digital era, the basic elements of this process, planning, organization, leadership and effective and efficient management of control systems in libraries contain important functions. The role of library leaders involves motivating and inspiring people to achieve the organizational objectives. Since new technologies are exploring day by day, there are significant changes occurring in libraries. However, the library retains its role as a repository of knowledge, organizing knowledge and providing access to it. Librarians as library leaders are supreme custodians of knowledge and partners to Learning and information resource, discovery and use. Librarians are crafting the path to idealize the vision, implement the mission, set strategic goals, and objectives to meet the effective Performance of the libraries. Effective leadership management depends on three basic personal skills: technical, human, and conceptual. This paper discusses about the characteristics of Library professional, skills needed for the Library leaders, various management techniques to be followed to achieve the objectives of Academic Libraries in the digital environment.